Effect of low skeletal muscle mass and sarcopenic obesity on chronic kidney disease in patients with type 2 diabetes. Issue 10 (5th September 2022) - Seo, Da Hea; Suh, Young Ju; Cho, Yongin; Ahn, Seong Hee; Seo, Seongha; Hong, Seongbin; Lee, Yong‐ho; Choi, Young Ju; Lee, Eunjig; Kim, So Hun
Abstract: Objective: This study aimed to investigate the association between low muscle mass or sarcopenic obesity and the risk of incident chronic kidney disease (CKD) in patients with type 2 diabetes mellitus (T2DM). Methods: A total of 3123 patients with T2DM with preserved renal function were followed up for incident CKD. Skeletal muscle mass was estimated from bioelectrical impedance analysis. CKD was defined as estimated glomerular filtration rate < 60 mL/min/1.73 m 2 . Sarcopenic obesity was defined as the coexistence of sarcopenia and abdominal obesity. Results: During 8.9 years of follow‐up, 530 (17.0%) patients developed incident CKD. When patients were divided into three groups based on sex‐specific tertiles, lower muscle mass was not associated with an increased risk of incident CKD after adjustment for risk factors. However, when patients were divided into four groups according to the presence of sarcopenia and obesity, sarcopenic obesity was associated with an increased risk of incident CKD (adjusted hazard ratio 1.77; 95% CI: 1.24‐2.51; p = 0.001) compared with the other groups. Conclusions: Sarcopenic obesity, but not low muscle mass alone, may increase the risk of CKD in patients with T2DM.